2014
DOI: 10.1007/s00167-014-2837-4
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of minimally invasive and conventional medial parapatella approaches for primary total knee arthroplasty

Abstract: Therapeutic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
(106 reference statements)
0
19
0
3
Order By: Relevance
“…First, the arthrotomy extended into the quadriceps tendon less than 4 cm above the upper pole of the patella in the MMP and QS groups but extended 6-8 cm in the MP group; second, the patella was everted from the beginning of the femoral resection to the end when patella resurfacing was performed in the MP group, whereas in the MMP and QS groups, the patella was not everted during the surgery. Many comparative studies of the MMP, QS and MP approaches have reported good clinical results but inferior lower limb mechanical axis and malposition at the shortterm follow-up for MMP [32,33] and QS [8,[34][35][36] because of the limited working space compared with the MP approach. In addition, some studies indicated that the MP approach may affect patellar tracking, AKP and the patellar position [8,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…First, the arthrotomy extended into the quadriceps tendon less than 4 cm above the upper pole of the patella in the MMP and QS groups but extended 6-8 cm in the MP group; second, the patella was everted from the beginning of the femoral resection to the end when patella resurfacing was performed in the MP group, whereas in the MMP and QS groups, the patella was not everted during the surgery. Many comparative studies of the MMP, QS and MP approaches have reported good clinical results but inferior lower limb mechanical axis and malposition at the shortterm follow-up for MMP [32,33] and QS [8,[34][35][36] because of the limited working space compared with the MP approach. In addition, some studies indicated that the MP approach may affect patellar tracking, AKP and the patellar position [8,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…However, results are still not conclusive. In general, MIS approaches appear to give better earlier flexion and/or range of motion [5258] although not for all MIS approaches [52, 53]. The majority showed earlier straight leg raise [52, 53, 55] but not all [54].…”
Section: Compare Conventional Surgical Technique Vs Mismentioning
confidence: 99%
“…In general, MIS approaches appear to give better earlier flexion and/or range of motion [5258] although not for all MIS approaches [52, 53]. The majority showed earlier straight leg raise [52, 53, 55] but not all [54]. MIS appears to improve immediate post-operative pain scores [52, 54] and early KSS [52, 53, 57] although one analysis found no difference in KSS [54].…”
Section: Compare Conventional Surgical Technique Vs Mismentioning
confidence: 99%
See 1 more Smart Citation
“…Las técnicas con incisiones mínimamente invasivas se van imponiendo por sus ventajas, al ser capaces de proporcionar una rehabilitación y recuperación funcional precoces. Las posibles complicaciones debidas al abordaje mínimo no parecen ser importantes y disminuyen a medida que aumenta la experiencia del cirujano y con el desarrollo de nuevos instrumentales quirúrgicos (50).…”
Section: Analgesia Multimodalunclassified